If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3)(x + -3) = (x + 4)(x + -2) Reorder the terms: (3 + x)(x + -3) = (x + 4)(x + -2) Reorder the terms: (3 + x)(-3 + x) = (x + 4)(x + -2) Multiply (3 + x) * (-3 + x) (3(-3 + x) + x(-3 + x)) = (x + 4)(x + -2) ((-3 * 3 + x * 3) + x(-3 + x)) = (x + 4)(x + -2) ((-9 + 3x) + x(-3 + x)) = (x + 4)(x + -2) (-9 + 3x + (-3 * x + x * x)) = (x + 4)(x + -2) (-9 + 3x + (-3x + x2)) = (x + 4)(x + -2) Combine like terms: 3x + -3x = 0 (-9 + 0 + x2) = (x + 4)(x + -2) (-9 + x2) = (x + 4)(x + -2) Reorder the terms: -9 + x2 = (4 + x)(x + -2) Reorder the terms: -9 + x2 = (4 + x)(-2 + x) Multiply (4 + x) * (-2 + x) -9 + x2 = (4(-2 + x) + x(-2 + x)) -9 + x2 = ((-2 * 4 + x * 4) + x(-2 + x)) -9 + x2 = ((-8 + 4x) + x(-2 + x)) -9 + x2 = (-8 + 4x + (-2 * x + x * x)) -9 + x2 = (-8 + 4x + (-2x + x2)) Combine like terms: 4x + -2x = 2x -9 + x2 = (-8 + 2x + x2) Add '-1x2' to each side of the equation. -9 + x2 + -1x2 = -8 + 2x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -9 + 0 = -8 + 2x + x2 + -1x2 -9 = -8 + 2x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -9 = -8 + 2x + 0 -9 = -8 + 2x Solving -9 = -8 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -9 + -2x = -8 + 2x + -2x Combine like terms: 2x + -2x = 0 -9 + -2x = -8 + 0 -9 + -2x = -8 Add '9' to each side of the equation. -9 + 9 + -2x = -8 + 9 Combine like terms: -9 + 9 = 0 0 + -2x = -8 + 9 -2x = -8 + 9 Combine like terms: -8 + 9 = 1 -2x = 1 Divide each side by '-2'. x = -0.5 Simplifying x = -0.5
| 8s^2+s-7=0 | | 3t-3(t+1)=t+2(t+1)+1 | | 5(2)=4y+16 | | 0.3x^2+1.8x+2.4=0 | | 6(w+2)-3=3-2(w-4) | | 5(3)=4y+16 | | 2x+3/2=3x-5/4 | | 11k+2=k^2 | | 5+2z= | | 5x=4(2)+16 | | -1.5p=-75 | | 49-9=5a | | (6x+1)(x+1)=(3x-2)(2x-5) | | 0.5j=5 | | 5x=4(1)+16 | | p^2+14p=0 | | 6m=15 | | -2.4p=7.2 | | 5x=4(0)+16 | | (m+10)(m+10)=15 | | (y-5)(y-5)=20 | | -2m=16 | | x^2+9x=-3 | | 8k=-64 | | -3r=-24 | | 4x-3=5x-1 | | -3t=51 | | 48+16=32 | | 4x^2-7x+19=9x+4 | | 8m=16 | | 20v^2-17v=63 | | 5(1)=4y+16 |